All happy families area alike: The EDPS' bridges between competition and privacy - Simonetta Vezzoso (Market and Competition Law Review)
Long before techlash became popular, the European Data Protection Supervisor (EDPS) was holding up a mirror to the EU competition authority. Not only the effectiveness of competition rules’ enforcement in the age of big data was questioned, but the suggestion was made to substantially improve the interaction, i.e. strengthen the family ties, between competition, data protection and consumer protection. The importance of this suggestion was recently acknowledged by the EU Commissioner and Executive Vice-President of the European Commission Margrethe Vestager at a lecture delivered in memorial of the former EDPS Giovanni Buttarelli: “[i]n this time of fast and radical change, all of us have a lot to learn from each other. And if we work together in the spirit that Giovanni Buttarelli showed us, we can achieve his cherished aim – a digital future that works for human beings.” The paper’s main purpose is to take stock of the current state of the interplay between data protection and competition law against the background of the roadmap presciently put forth by the EDPS since 2014. Moreover, in the spirit that Giovanni Buttarelli showed us, it is suggested that new forms of collaborative enforcement should be explored, the workings of the Digital Clearinghouse progressively institutionalised, also at national level, and, most importantly, that a pro-competitive data governance framework should be developed in a cooperative manner. The paper’s main purpose is to take stock of the current state of the interplay between data protection and competition law against the background of the roadmap presciently put forth by the EDPS since 2014. Moreover, in the spirit that Giovanni Buttarelli showed us, it is suggested that new forms of collaborative enforcement should be explored, the workings of the Digital Clearinghouse progressively institutionalised, also at national level, and, most importantly, that a pro-competitive data governance framework should be developed in a cooperative manner.